DAMPAK EKONOMI IMPLEMENTASI PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) PADA PERUM PERHUTANI UNIT II JAWA TIMUR - Theresia Avila; Bambang Suyadi (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2015)
This research was conducted to determine the economic impact of the implementation program community based forest management (CBFM). This program collaboration between Institute Perhutani and local institutions (Lembaga Masyarakat Desa Hutan (LMDH) Petani Hutan Lestari which become as a partner. The purpose of this study was to determine the increase in income that is felt by the villagers Grajagan incorporated in Sustainable Forest Farmers LMDH. This research is a descriptive quantitative research. The place of the research is determined by using purposive area method and result Grajagan village as the location. Data collection of the research used interview, observation, and documents method. The results showed that the CBFM program Perhutani economic impact by increasing the income of rural communities in Grajagan. It is obtained from tumpangsari system, the additional work in forestry so that people get an additional wage and also any profit sharing that can increase the income of rural communities.